Clinical impact of whole-body 68Ga-PSMA I&T PET/CT: lesion frequency and added benefit in lower extremities - Stolzenbach, Lara Franziska; Löcherbach, Florian; Wargenau, Katharina; Pose, Randi; Steuber, Thomas; Tian, Zhe; Budäus, Lars; Tilki, Derya; Graefen, Markus; Köhler, Daniel; Karakiewicz, Pierre I.; Sauer, Markus; Apostolova, Ivayla Ilieva; Maurer, Tobias; Berliner, Christoph (Nuklearmedizin - NuclearMedicine, 2021)
Aim Few small-scaled studies performed systematic analysis of the benefits of extending prostate specific membrane antigen positron-emission tomography/ computed tomography (68Ga-PSMA I&T PET/CT) to the lower extremities in prostate cancer (PCa) patients. We hypothesized that 68Ga-PSMA I&T PET/CT positive lesions are rare in lower extremities of prostate cancer (PCa) patients, the clinical implication is negligible and may therefore be omitted.Methods We retrospectively analyzed 1,068 PCa patients who received 68Ga-PSMA I&T PET/CT in a single institution (2016–2018). Of those, 285 (26.7%) were newly diagnosed, 529 (49.5%) had biochemical recurrence (BCR) and 254 (23.8%) were castration-resistant prostate cancer (CRPC) patients.Results Of 1,068 68Ga-PSMA I&T PET/CTs, positive lesions in the lower extremities were identified in 6.9% patients (n=74). Positive lesions in the lower extremities were most common in CRPC patients (19.7%; n=50), followed by newly diagnosed (3.2%; n=9) and BCR (2.8%; n=15) PCa patients. Only 3 patients presented with exclusive lesions in the lower extremities, respectively 0.8% (n=2) in CRPC and 0.4% (n=1) in newly diagnosed PCa. Both CRPC (94.1%, n=47) and BCR (80.0%, n=12) patients with PSMA-positive lesions predominantly received systemic therapy.Conclusion Identification of lower extremities lesions with PSMA PET/CT is uncommon and exclusive lesions are rare. PSMA PET/CT findings of the lower extremities did not change therapy management. Thus, scanning of the lower extremities can be omitted in standard protocols.
Keywords: Prostatakarzinom; Knochenmetastasen; biochemisches Rezidiv; CRPC; PSMA-PET/CT; primäres Staging